DEVELOPING TEACHER PROFESSIONALSM COMPETENCIES THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGY DIGITALIZATION TRAINING - Andarto, Benedictus Audy; Relawati, Laditia Dilah; Darmawan, Wewen; Ramadhan, Iwan (LPPM Univ. Ibn Khaldun Bogor, 2024)
This activity aims to investigate the development of competencies of teachers at SMA Negeri 9 Pontianak through Artificial Intelligence (AI) technology training. The method used in this research involves training and mentoring in creating AI products. The teachers are provided with an introduction and explanation of the advantages, disadvantages, benefits, and steps in using AI. They are then given the opportunity to use AI in creating learning products. The results of this activity indicate that AI technology training can empower teachers in enhancing their skills in creating learning products. Teachers can integrate AI into the learning process. This activity provides an important contribution to understanding the development of teacher competencies through AI training. The practical implication of this activity is the importance of developing teacher competencies to face technological advancements in the field of education.